Sex Differences in Traumatic Brain Injury: What We Know and What We Should Know - Gupte, Raeesa P.; Brooks, William M.; Vukas, Rachel R.; Pierce, Janet D.; Harris, Janna L. (Journal of neurotrauma, 2019)
There is growing recognition of the problem of male bias in neuroscience research, including in the field of traumatic brain injury (TBI) where fewer women than men are recruited to clinical trials and male rodents have predominantly been used as an experimental injury model. Despite TBI being a leading cause of mortality and disability worldwide, sex differences in pathophysiology and recovery are poorly understood, limiting clinical care and successful drug development. Given growing interest in sex as a biological variable affecting injury outcomes and treatment efficacy, there is a clear need to summarize sex differences in TBI. This scoping review presents an overview of current knowledge of sex differences in TBI and a comparison of human and animal studies. We found that overall, human studies report worse outcomes in women than men, whereas animal studies report better outcomes in females than males. However, closer examination shows that multiple factors including injury severity, sample size, and experimental injury model may differentially interact with sex to affect TBI outcomes. Additionally, we explore how sex differences in mitochondrial structure and function might contribute to possible sex differences in TBI outcomes. We propose recommendations for future investigations of sex differences in TBI, which we hope will lead to improved patient management, prognosis, and translation of therapies from bench to bedside.